Rosie Revere, engineer - Beaty, Andrea (Children's Braille Book Club, 2013)
Where some people see rubbish, Rosie Revere sees inspiration. Alone in her room at night, shy Rosie constructs great inventions from odds and ends. Hot dog dispensers, helium pants, python-repelling cheese hats: Rosie's gizmos would astound - if she ever let anyone see them. Afraid of failure, she hides them away under her bed. Until a fateful visit from her great-great-aunt Rose who shows her that a first flop isn't something to fear - it's something to celebrate.